Proposta de experimentação de baixo custo no ensino de física - PEREIRA, Josimara Lobato (2022)
The objective of this work is to approach and analyze the question of the use of experimentation in the teaching of physics, with proposals for low-cost experiments, in order to encourage teachers to use the experiments in physics classes, and also to promote the active participation of students in classes. To obtain these proposed objectives, the literature review methodology was used in articles, theses, dissertations, focused on this theme. According to the researches analyzed, the teaching of physics faces a very difficult reality, as the classes are still predominantly theoretical, with expository classes, unattractive and far from the students’ reality, making them not interested in the subject, as the classes they come down to the application of formulas and concepts. As a result, researchers and educators have advocated the use of experimentation as an effective tool for stimulating student interest in the discipline. In general, experimentation is rarely present in Physics classes, due to the lack of laboratory, equipment, and teacher training, or when it is used it is wrongly used. Thus, one of the alternatives defended by the authors to face the lack of equipment and also the lack of a laboratory, is the planning and execution of low-cost experimental activities. Experimentation in teaching physics is still a challeng to be overcome. Despite this, most of the Works analyzed showed a poitive rather than a negative view of expeimentation in teaching physics.